Development of interactive E-Modules on entrepreneurship based on augmented reality for students of SMKN 6 Medan - Tarigan, Hermelina Eka Sari br; Manullang, Jontinus; Ginting, Bena br; Situmorang, Julianto (Journal of Intelligent Decision Support System (IDSS), 2025)
Entrepreneurship education in vocational high schools (SMK) is often dominated by conventional methods that make students passive and less able to connect theory with practice, especially on abstract topics such as franchising. This study aims to develop an Augmented Reality (AR)-based entrepreneurship e-Module that is interactive, contextual, and oriented toward vocational learning. Using a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study involved 100 grade XI students at SMK Negeri 6 Medan. Data were collected through expert validation, questionnaires, observations, interviews, and pre- and post-tests. The validation results placed the e-Module in the highly valid category (>80%), while the N-gain test showed a significant increase in the experimental class (0.83; high category) compared to the control class (0.32; low category). The t-test also confirmed a significant difference (p < 0.05) between the two groups. In addition, observations indicated improvements in student motivation, engagement, and understanding, as well as greater ease for teachers in delivering abstract material. These findings demonstrate that AR integration in entrepreneurship e-Modules can effectively bridge theory and practice, enhance learning quality in vocational schools, and support the achievement of SDG 4 on quality education.